Optimization of a multi-echelon sustainable production-distribution supply chain system with lead time consideration under carbon emission policies. (September 2019) - Manupati, V.K.; Jedidah, Sivakumar Jane; Gupta, Shreya; Bhandari, Aditi; Ramkumar, M.
Highlights: Reviewed production distribution problems in the context of multi-echelon supply chain. Investigate the carbon policies on production, distribution and inventory control decisions. A non-linear mixed integer programming model has been developed. A heuristic algorithm has been proposed for finding the optimal solutions. Abstract: Nowadays, sustainability has gained much attention from economists, environmentalists, consumers, industrialists, government and the academia. The regulatory policies for carbon emissions force the firms to redesign its supply chain. In this paper, different production-distribution and inventory problems in multi-echelon supply chain were critically investigated with three carbon policies (carbon tax, strict carbon capping and carbon cap-and-trade) and lead-time considerations. Then, a non-linear mixed-integer programming based mathematical model has been developed and tested with the proposed heuristic. The obtained results demonstrate the robust performance of the proposed algorithm that can further help the policy makers and experts for designing and evaluation of sustainable supply chain.